Examination of the latent structure of DSM-5 posttraumatic stress disorder symptoms in Slovakia. (September 2018) - Ross, Jana; Kaliská, Lada; Halama, Peter; Lajčiaková, Petra; Armour, Cherie
Highlights: Six-factor Anhedonia model provided the best fit to the data. Anhedonia model's factors show differential relationships with external constructs. Avoidance factor is distinct from anhedonia and negative affect factors. Anxious arousal factor is distinct from dysphoric arousal factor. Depression is more strongly related to anhedonia than the negative affect factor. Abstract: The latent structure of posttraumatic stress disorder (PTSD) has been widely discussed, with the majority of studies in this area being conducted in the US. The current study aimed to extend this area of research by comparing seven existing PTSD factor models in a sample of 754 trauma-exposed university students from Slovakia, where similar research has not been conducted yet. The sample was predominantly female (83.69%), with a mean age of 22.68 years. The comparison of competing models revealed that the Anhedonia model, consisting of six inter-correlated factors of reexperiencing, avoidance, negative affect, anhedonia, dysphoric arousal and anxious arousal, provided the best fit. Several factors of the Anhedonia model also showed differential relationships with the external variables of anxiety and depression. The study contributes to the limited literature on the latent structure of PTSD in Eastern Europe.